Pengaruh Public Speaking Pemimpin Terhadap Kinerja Awak Kapal - kuncowati kuncowati; S. Teguh Wiyono (Sekolah Tinggi Maritim Yogyakarta, 2021)
The ability of the leader ( Master, Head Of Engine Room, Deck Officer, Engine Officer) when watchkeeping on board requires not only knowledge, skills but also various theories, techiques, methods in public speaking so as to be able to speak, convey message, information and orders to the men in the guard work squad on board well so that communication runs smoothly and eliminates misunderstandings so that the performance on the ship that has been targeted is achieved. The Study aims to analisys the infuance of public speaking leaders on the performance of the crew. This study uses quanttative method with linear regression analisys with test-t. Respondent in this study is the crew of commercial ship that is in the Port of Tanjung Perak Surabaya with total 0f 80 ( eighty) respondents. The result of this study based on linear regression and t test is that the public speaking faktor of the leader has a positive and significant effect of 0.610 units on the performance of the crew and based on the determination test obtained by the public speaking factor the leader affect 37.1% of the crew’s performance.